Neuroprotective effect of dexmedetomidine on autophagy in mice administered intracerebroventricular injections of Aβ25–35 - Lee, Youn Young; Han, Jong In; Lee, Kyung Eun; Cho, Sooyoung; Suh, Eun Cheng (Frontiers in Pharmacology, 2023)
Alzheimer's disease (AD), one of the most prevalent neurodegenerative diseases is associated with pathological autophagy-lysosomal pathway dysfunction. Dexmedetomidine (Dex) has been suggested as an adjuvant to general anesthesia with advantages in reducing the incidence of postoperative cognitive dysfunction in Dex-treated patients with AD and older individuals. Several studies reported that Dex improved memory; however, evidence on the effects of Dex on neuronal autophagy dysfunction in the AD model is lacking. We hypothesized that Dex administration would have neuroprotective effects by improving pathological autophagy dysfunction in mice that received an intracerebroventricular (i.c.v.) injection of amyloid βprotein fragment [25][26][27][28][29][30][31][32][33][34][35] and in an autophagy-deficient cellular model. In the Y-maze test, Dex reversed the decreased activity of Aβ25-35 mice. Additionally, it restored the levels of two memory-related proteins, phosphorylated Ca 2+ /calmodulin-dependent protein kinase II (p-CaMKII) and postsynaptic density-95 (PSD-95) in Aβ25-35 mice and organotypic hippocampal slice culture (OHSC) with Aβ25-35. Dex administration also resulted in decreased expression of the autophagy-related microtubule-associated proteins light chain 3-II (LC3-II), p62, lysosomeassociated membrane protein2 (LAMP2), and cathepsin D in Aβ25-35 mice and OHSC with Aβ25-35. Increased numbers of co-localized puncta of LC3-LAMP2 or LC3-cathepsin D, along with dissociated LC3-p62 immunoreactivity following Dex treatment, were observed. These findings were consistent with the results of western blots and the transformation of doublemembrane autophagosomes into single-membraned autolysosomes in ultrastructures. It was evident that Dex treatment alleviated impaired autolysosome formation in Aβ mice. Our study demonstrated the improvement of memory impairment caused by Dex and its neuroprotective mechanism by investigating the role of the autophagy-lysosomal pathway in a murine Aβ25-35 model. These findings suggest that Dex could be used as a potential neuroprotective adjuvant in general anesthesia to prevent cognitive decline.